Outside directors, board interlocks and firm performance: Empirical evidence from Colombian business groups (2011)
We investigate the relation of board structure through the appointments of outside directors and the role of busy directors on firm return on assets within an environment of no regulation for privately held firms and voluntary adoption of corporate best practices for security issuers with family controlling blockholders. This study relies on a sample of an average of 335 firms per year for the 1996-2006 period, where 244 are private firms and 285 are affiliated to one of the seven largest non-financial business groups in the country. Five of these groups were, in 2006, still family-controlled. We find a positive relation between both the ratio of outside directors, and the degree of board interlocks, with firm return-on-assets. Outside busy directors turned out to be key drivers of improved firm performance. Appointments of outsiders are endogenous to firm ownership structure. Blockholder activism as well as contestability becomes an internal mechanism that improves director monitoring and ex-post firm valuation. © 2011 Elsevier Inc.